Ice sheet extension to the Celtic Sea shelf edge at the Last Glacial Maximum. (1st March 2015) - Praeg, Daniel; McCarron, Stephen; Dove, Dayton; Ó Cofaigh, Colm; Scott, Gill; Monteys, Xavier; Facchin, Lorenzo; Romeo, Roberto; Coxon, Peter
Abstract: Previous reconstructions of the British–Irish Ice Sheet (BIIS) envisage ice streaming from the Irish Sea to the Celtic Sea at the Last Glacial Maximum, to a limit on the mid-shelf of the Irish-UK sectors. We present evidence from sediment cores and geophysical profiles that the BIIS extended 150 km farther seaward to reach the continental shelf edge. Three cores recently acquired from the flank of outer Cockburn Bank, a shelf-crossing sediment ridge, terminated in an eroded glacigenic layer including two facies: overconsolidated stratified diamicts; and finely-bedded muddy sand containing micro- and macrofossil species of cold water affinities. We interpret these facies to result from subglacial deformation and glacimarine deposition from turbid meltwater plumes. A date of 24, 265 ± 195 cal BP on a chipped but unabraded mollusc valve in the glacimarine sediments indicates withdrawal of a tidewater ice sheet margin from the shelf edge by this time, consistent with evidence from deep-sea cores for ice-rafted debris peaks of Celtic Sea provenance between 25.5 and 23.4 ka BP. Together with terrestrial evidence, this supports rapid (ca 2 ka) purging of the BIIS by an ice stream that advanced from the Irish Sea to the shelf edge and collapsed back during Heinrich event 2. Highlights: First cores of glacigenic sediments from the Celtic Sea shelf in over 35 years and first radiometric determination of their age. Flank of outer Cockburn Bank capped by overconsolidated stratified diamicts and undeformed muddy sand with cold water fauna. Eroded sheet of subglacially deformed to glacimarine deposits interpreted to be present along the Irish-UK shelf edge. Imply the British–Irish Ice Sheet to have extended 150 km farther seaward than previously proposed limits. Consistent with purging of the Irish Sea Ice Stream during rapid advance and retreat ca 23–25 ka.